Security issues in cloud computing using edge computing and blockchain: Threat, mitigation, and future trends-a systematic literature review - Ahmad Khan, Muzammil; Mehmood Khan, Shariq; Subramaniam, Siva Kumar (University of Malaya, 2023)
Within the neoteric decade, cloud computing has grown as emerging technology which is an on-demand availability of network resources, particularly data storage without any management by users. However, the occurrence of security threats and vulnerability has gradually increased in this processing technology due to its notable growth. In addition to that, he existing Systematic Literature Reviews (SLRs) are only limited with cloud related issues and does not provides their impact on other technologies. This Systematic Literature Review (SLR) examines the security threats experienced by cloud computing along with QoS by edge computing and scheduling. Various consumers and cloud service providers (CSP) obtained benefits from the cloud computing environment. However, various privacy and security challenges occur in this digital age. This SLR mainly aims to review the state of the art research studies on secure cloud computing with high QoS and its challenges. This SLR examined numerous research studies related to cloud computing security with secure service level agreement (SLA) which are published between 2019 to 2022 from the reputed electronic databases. Cloud computing security is ensured mostly based on trust evaluation, implementation of blockchain technology, authentication, and cryptography techniques, and implementing edge computing in the cloud environment. This SLR also analyzed the research gaps of the previous research papers and provides future research directions to obtain secure cloud computing environment with high QoS performance.